Função de mapeamento brasileira da atmosfera neutra e sua aplicação no posicionamento GNSS na América do Sul - Gouveia, Tayná Aparecida Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Global Navigation Satellite Systems (GNSS) technology has been widely used in positioning, from day-to-day applications (metric accuracy) to applications that require high accuracy (few cm or dm). For high accuracy, different techniques may be applied to minimize the effects that the signal suffers from its transmission on the satellite to its reception. GNSS signal when propagating in the neutral atmosphere (from surface up to 50km) is influenced by hydrostatic gases and water vapor. The variation of these atmospheric constituents causes a refraction in the signal that generates a delay. This delay may cause errors of at least 2.5 m (zenith) and greater than 25 m (slant). The determination of the delay in the slanted direction (satellitereceiver) according to the elevation angle is performed by the mapping functions. One of the techniques for calculating the delay is raytracing. This technique allows us to map the actual path that the signal has traveled and to model the interference of the neutral atmosphere on it. Different approaches can be used to obtain information describing the neutral atmosphere constituents - temperature, pressure and humidity. The possibilities include the use of radiosonde measurements, weather and climate models (NWP), GNSS measurements, as well as theoretical models. Regional NWP models from the Center Weather Forecasting and Climate Studies (CPTEC) of the National Institute for Space Research (INPE) are a good alternative to provide atmospheric measurements, which describe the highly variable climate, according to the season and region of Brazil. In this research, these measurements were obtained from the NWP model of higher temporal (hourly) and spatial (5km) resolution, which started operations in 2018 as a regional model by CPTEC/INPE, named Weather Research and Forecasting (WRF). Considering the atmospheric variables obtained from the WRF, by applying the raytracing technique, the neutral atmosphere mapping function for Brazil and South America was developed, named Brazilian Mapping Function (BMF). BMF was used to obtain the knowledge and develop this methodology, which so far had not been carried out in Brazil. This function was evaluated in two approaches: regarding the quality of the delay; and precise point positioning (PPP) quality using BMF. In the first assessment of the zenith delay, we considered as reference the results from radiosonde and from data of four stations of the Brazilian Network for Continuous Monitoring of the GNSS Systems (RBMC), located in regions with distinct climatic characteristics (NAUS; CUIB; POLI; POAL). The period assessed was of one year of data, through which it was possible to verify the quality of the function in computing the zenith delay in the different seasons of the year. These results showed that the zenith delay obtained from BMF presented a maximum RMSE of 6 cm (in POAL) in relation to the reference data. Delay and inclined factor series were also generated, although they did not have reference data for statistical evaluation. They showed similar variability to the zenith delay (factor is the ratio between the inclined and zenith delays). In addition to these assessments, a preliminary analysis was performed to evaluate the contribution of BMF in PPP, with different strategies: one day of data processing; two stations; PPP static and kinematic mode; and different initialization times. In the quality assessment, the Vienna Mapping Function 1 (VMF1) was considered as a reference, whose results are from the global model of the European Center for Medium-Range Weather Forecasts (ECMWF). BMF also showed promising results for the post-processing positioning mode of high accuracy in the evaluated Brazilian regions. The best performance was obtained when it was applied to determine the a priori value of the PPP delay estimate, and closest to the NWP model analysis, the WRF at 12 UTC.

A tecnologia Global Navigation Satellite Systems (GNSS) tem sido amplamente utilizada em posicionamento, desde as aplicações cotidianas (acurácia métrica), até aplicações que requerem alta acurácia (poucos cm ou dm). Quando se pretende obter alta acurácia, diferentes técnicas devem ser aplicadas a fim de minimizar os efeitos que o sinal sofre desde sua transmissão, no satélite, até sua recepção. O sinal GNSS ao se propagar na atmosfera neutra (da superfície até 50 km), é afetado por gases hidrostáticos e vapor d’água. A variação desses constituintes atmosféricos causa uma refração no sinal que gera um atraso. Esse atraso pode ocasionar erros na medida de no mínimo 2,5 m (zenital) e superior a 25 m (inclinado). A determinação do atraso na direção inclinada (satélite-receptor) de acordo com o ângulo de elevação é realizada pelas funções de mapeamento. Uma das técnicas para o cálculo do atraso é o traçado de raio (ray tracing). Essa técnica permite mapear o caminho real que o sinal percorreu e modelar a interferência da atmosfera neutra sobre esse sinal. Diferentes abordagens podem ser usadas para obter informações que descrevem os constituintes da atmosfera neutra. Dentre as possibilidades pode-se citar o uso de medidas de radiossondas, modelos de previsão do tempo e clima (PNT), medidas GNSS, assim como modelos teóricos. Modelos de PNT regionais do Centro de Previsão de Tempo e Estudos Climáticos (CPTEC) do Instituto Nacional de Pesquisas Espaciais (INPE) apresentam-se como uma boa alternativa para disponibilizar as medidas atmosféricas, que descrevem o clima altamente variável, de acordo com a época e região do Brasil. Nessa pesquisa, essas medidas foram obtidas a partir do modelo de PNT de maior resolução temporal (horária) e espacial (5km), adotado em 2018 como modelo operacional regional pelo CPTEC/INPE, denominado Weather Research and Forecasting (WRF). Com as variáveis atmosféricas obtidas a partir do WRF foi aplicada a técnica de traçado de raio possibilitando o desenvolvimento de uma função de mapeamento da atmosfera neutra, para o Brasil e América do Sul, denominada Brazilian Mapping Function (BMF). A partir da função de mapeamento desenvolvida foi possível obter o conhecimento e desenvolver essa metodologia, até então não realizado no Brasil. Essa função foi avaliada em duas abordagens: em relação à qualidade do atraso; e aplicação no posicionamento por ponto preciso (PPP). Na primeira avaliação considerou-se como medidas de referência dados de radiossondas, em quatro estações da Rede Brasileira de Monitoramento Contínuo dos Sistemas GNSS (RBMC), localizadas em regiões com características climáticas distintas (NAUS, CUIB, POLI, POAL). O período avaliado constituiu um ano de dados, por meio do qual foi possível verificar a qualidade da função na determinação do atraso zenital nas diferentes estações do ano. Esses resultados mostraram que o atraso zenital obtido a partir da BMF apresentou REQM de no máximo 6 cm (em POAL) em relação aos dados de referência. Também foram geradas séries do atraso e fator inclinado, embora não tivessem dados de referência para avaliação estatística, apresentaram variabilidade semelhante ao atraso zenital. Além dessas análises, uma análise preliminar foi realizada para avaliar a BMF no PPP, com diferentes estratégias: duas estações; PPP modo estático e cinemático; e diferentes épocas de inicialização. Para avaliar a qualidade do mesmo, considerou-se como referência o modelo mais recomendado para uso, a Vienna Mapping Function 1 (VMF1) que resulta do modelo global de PNT do European Centre for Medium- Range Weather Forecasts (ECMWF). A BMF apresentou resultados promissores no posicionamento pós processado de alta acurácia nas regiões brasileiras avaliadas. O melhor desempenho da BMF foi obtido quando aplicada na determinação dos valores a priori na estimativa do atraso no PPP e mais próximo da análise do modelo de PNT, o WRF às 12 UTC.
A Brazilian mapping function of the neutral atmosphere and application for GNSS positioning in South America
Keywords: Mapping function; Ray tracing; Neutral atmosphere modeling; Regional NWP; GNSS PPP; Função de mapeamento; Traçado de raio; Modelagem da atmosfera neutra; PNT regional; PPP GNSS